Peningkatan Hasil Belajar Fisika Dengan Metode Pembelajaran Brainstorming - Aristawati, Ika Vidiasari (Universitas Nusantara PGRI Kediri, 2020)
Classroom Action research is against the background of the lack of activeness of the students, especially class X TKRO 01 SMK Negeri 1 Trenggalek school year 2018/2019 in the scientific attitude and mastery learning classical low. Based on the acquisition of the data, the percentage of student activity 42,86 %. Because it then affects the learning outcomes of students who tend to be low around 54,29 % of the expected result or the limit of the minimum standard of completeness. It is based on obtaining the results of the study on previous material. This research method used the research model to adapt the combined Sanford and Kemmis using classroom action research. The study was conducted in two cycles: one cycle is performed as much as two times the action research. The subject of research is class X TKRO 01 as many as 35 students. Data collection techniques in this research using observation and test. Data in the form of learning outcomes in the form of assessment of the third aspect, among others, attitude, skills, knowledge with the use of instruments as appropriate. The results of the test in cycle I based on the data acquisition of the percentage of mastery learning classical reached 74,29 % with the average results of the acquisition value 71,81. The percentage of mastery the standards mastery minimum in the classical style. While for the assessment of the activity, the percentage of active students in scientific attitude to achieve 71,43 % with the number of students active in 25 of the 35 students. Assessment of skills to achieve the percentage of 71,43 % with the average value of the skills of 63,81. The results of the test in cycle II data based on the acquisition of the percentage of mastery learning classical reached 85,71 % with the average results of the acquisition value 76,00. While for the assessment of the activity, the percentage of active students in scientific attitude reached 85,71 % with the number of students active 30 of 35 students and assessment of skills to achieve the percentage of 82,86 % with the average value of the skills of 77,14. Based on the acquisition of a percentage of the value of the learning result from cycle I and cycle II increased by 11,42 % to the value of knowledge, while the liveliness of the students in the scientific attitude increased by 11,43 %, while the skills of students increased by 14,28 %, so learning the methods of brainstorming can improve student learning outcomes.